2015
DOI: 10.14534/pucr.2015410990
|View full text |Cite
|
Sign up to set email alerts
|

Omphalocele, exstrophy of cloaca, imperforate anus and spinal defect (OEIS Complex): A case report

Abstract: Omphalocele, exstrophy of cloaca, imperforate anus and spinal defect (OEIS Complex) is an extremely rare combination of serious defects, which was firstly described by Carey and colleagues. Surgical repair of cloacal exctrophy in patients with OEIS complex can be performed at one stage, but it can also be performed safely as staged to minimize the potential complications. In this case report, we aimed to present our early approach to the OEIS complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The major etiology of failure is severe symphysis diastasis causing inadequate approximation of the pubic bones and tight closure of large abdominal defects leading to organ ischemia. 6 In our case, we have separated and repaired the fused cecum and bladder with the insertion of a 4 Fr size feeding tube in the left ureter. The ladd procedure was done.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The major etiology of failure is severe symphysis diastasis causing inadequate approximation of the pubic bones and tight closure of large abdominal defects leading to organ ischemia. 6 In our case, we have separated and repaired the fused cecum and bladder with the insertion of a 4 Fr size feeding tube in the left ureter. The ladd procedure was done.…”
Section: Discussionmentioning
confidence: 95%
“…Surgical repair is always challenging due to the complexity of these malformations and requires that multidisciplinary teams include neonatologists, pediatric surgeons, pediatric urologists, pediatric orthopedists, pediatric neurosurgeons, and genetic and pediatric endocrinologists. 6,7 The goals of OEIS management are; separating the bowel from the bladders to create an intestinal stoma, closing the omphalocele, an adaptation of the bladder halves, and adequate cosmetic and functional urogenital reconstructions with preserving renal function. The surgical treatment of OEIS can be achieved in single or multiple stages with an increasing preference towards the staged approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In several studies, it has been demonstrated that the application of a barrier dressing and frequent irrigation can preserve the bladder mucosa ( 11 , 12 ). In one study in 2015, it has been demonstrated that plastic coverage during all follow-up period prevented the thickening of the mucosa and polyp formation and prevented prolonged environmental exposure of the bladder mucosa ( 13 ). In the present study, it was shown that the application of PVdC as an appropriate wrap may decrease the size and number of polyps.…”
Section: Discussionmentioning
confidence: 99%